Pengaruh risiko operasional dan tingkat kecukupan modal terhadap profitabilitas pada bank umum swasta nasional di bursa efek indonesia periode 2015-2019 - Krisma Aprilita Yuniar; Gusganda Suria Manda (Jurnal Riset Pendidikan Ekonomi, 2021)
Banks are financial institutions whose activities are to collect funds (money) from the public in the form of deposits. Profitability in a bank is influenced by several factors, including operational risk and the level of capital adequacy. The purpose of this study was to determine the effect of Operational Risk and Capital Adequacy Ratio on Profitability at Bank Milik Swasta Nasional listed on the Indonesian Stock Exchange for the period 2015-2019. This study uses a population of 6 private banks listed on the IDX with a total of 30, sampling on the IDX accessed through the website www.idx.co.id and data obtained in the form of published Private Bank Annual Report. The data analysis technique used is Descriptive Analysis, Classical Assumption Test, Multiple Linear Regression Analysis and Hypothesis Test (t and f test). The results of this study indicate that operational risk has a significant negative effect on profitability, and the level of capital adequacy has a significant positive effect on profitability.